Binder polymer, positive pole piece, battery and electric equipment

By designing a binder polymer containing rigid, flexible and polar monomers, the problems of low adhesion and poor ion diffusion of the existing sulfide solid-state battery binder are solved, and the high mechanical properties of the positive electrode sheet are achieved Performance and electrochemical properties.

CN119463023AInactive Publication Date: 2025-02-18BYD CO LTD

Patent Information

Application Number
CN202411540311.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing adhesives suitable for sulfide solid state batteries have problems such as low adhesion and poor ion diffusion, which is difficult to meet the high-performance needs of batteries.

Method used

A binder polymer containing rigid, flexible and polar monomers is proposed. Through reasonable monomer ratio and structural design, the adhesiveness, flexibility and dispersion of the binder are improved, thereby enhancing the positive electrode sheet. Mechanical and electrochemical properties.

Benefits of technology

The binder polymer can effectively disperse the main material, improve the stability and mechanical properties of the electrode slurry, enhance the peeling force and electrochemical properties of the electrode sheet, and improve the performance of the positive electrode sheet as a whole.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005113784220000021
    Figure BDA0005113784220000021
  • Figure BDA0005113784220000023
    Figure BDA0005113784220000023
  • Figure BDA0005113784220000024
    Figure BDA0005113784220000024
Patent Text Reader

Abstract

The invention provides a binder polymer, a positive pole piece, a battery and electric equipment, the monomer of the binder polymer comprises: a rigid monomer, the rigid monomer has at least one of the following substituted or unsubstituted groups: C6-C12 aryl, C3-C11 heteroaryl, C4-C8 cycloalkyl or C3-C7 heterocyclic group; a flexible monomer, wherein the flexible monomer has a substituted or unsubstituted C2-C30 alkenyl group; and a polar monomer having an ester group. The binder polymer disclosed by the invention has good adhesion, flexibility and dispersity, and is beneficial to ion and electron transmission, so that the positive pole piece has excellent mechanical property, processability and electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a binder polymer, a positive electrode sheet, a battery and an electrical device. Background Art

[0002] Solid-state batteries usually refer to battery devices that include a positive electrode sheet, a negative electrode sheet, and a solid electrolyte layer located between the two. Binders, as one of the main components of solid-state batteries, may exist in the solid electrolyte layer or the active material layer of the electrode sheet. The main purpose of the binder is to bind solid electrolyte particles, electrode active substances and other components to prevent these components from detaching from battery components such as electrode sheets. Sulfide solid-state batteries have attracted widespread attention from academia and industry due to their high energy density and high safety. However, the binders currently suitable for sulfide solid-state batteries still have defects such as low adhesion and poor ion diffusion, which still need to be studied. Summary of the invention

[0003] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, one purpose of the present application is to propose a binder polymer, a positive electrode sheet, a battery and an electrical device. The binder polymer of the present application has good adhesion, flexibility and dispersibility, is conducive to ion and electron transmission, and makes the positive electrode sheet have excellent mechanical properties, processing properties and electrochemical properties.

[0004] The first aspect of the present application provides a binder polymer. According to an embodiment of the present application, the monomers of the binder polymer include:

[0005] A rigid monomer having at least one of the following substituted or unsubstituted groups: C6 to C 12 Aryl, C3~C 11 Heteroaryl, C4-C8 cycloalkyl or C3-C7 heterocyclic group;

[0006] A flexible monomer having a substituted or unsubstituted C2 to C 30 alkenyl;

[0007] A polar monomer having an ester group.

[0008] The binder polymer according to the embodiment of the present application includes a rigid monomer, a flexible monomer and a polar monomer, wherein the rigid monomer has a high T g , can effectively disperse the main materials (including positive electrode active materials and sulfide solid electrolytes, etc.), thereby improving the stability of the electrode slurry, the slurry viscosity changes little, and the thixotropy is good; the flexible monomer has a low T g, which can make the binder polymer be stretched or shrunk well, so that the pole piece has good mechanical properties and processing properties; the introduction of ester groups in polar monomers can increase the polarity of the binder polymer, improve the interaction between the binder polymer and the main material, and increase the peeling force of the pole piece. In addition, the ester group is stable to the sulfide solid electrolyte, and will continuously react with lithium ions under the action of the electric field, which is beneficial to the diffusion of lithium ions. In this way, the mechanical properties and electrochemical properties of the positive pole piece can be improved as a whole.

[0009] According to an embodiment of the present application, the rigid monomer has a structure as shown in formula (1),

[0010]

[0011] Wherein, R1 is selected from the following substituted or unsubstituted groups: C6~C 12 Aryl, C3~C 11 Heteroaryl, C4-C8 cycloalkyl or C3-C7 heterocyclic group;

[0012] R2, R3 and R4 are each independently selected from -H, -F, -Cl, Br, -I, substituted or unsubstituted -(CH2) i -CH3, i is an integer from 0 to 20;

[0013] The substituted substituent is selected from halogen, ester, C1-C 10 Alkyl or C6~C 12 Cycloalkyl.

[0014] According to an embodiment of the present application, R1 is selected from

[0015] R1' is selected from C1-C4 alkyl;

[0016] C3~C 11 The heteroatoms of the heteroaryl group and the C3-C7 heterocyclic group are each independently selected from O, S or N;

[0017] The ester group is selected from methyl formate, ethyl formate, butyl formate, methyl sulfonate, ethyl sulfonate or propyl sulfonate;

[0018] i is an integer from 0 to 3.

[0019] According to an embodiment of the present application, a lithium acetate group is connected to the main chain of the rigid monomer.

[0020] According to an embodiment of the present application, the rigid monomer has any of the following structures:

[0021]

[0022] According to an embodiment of the present application, the flexible monomer has a structure as shown in formula (2),

[0023]

[0024] Wherein, R5, R6, R7 and R8 are each independently selected from -H, -F, -Cl, Br, -I, -CN, -COOR, -SO2OR, substituted or unsubstituted -(CH2) j -CH3;

[0025] R is selected from C1-C6 alkyl;

[0026] j is an integer from 0 to 20;

[0027] The substituted substituent is selected from halogen, ester, C1-C 10 Alkyl, C6~C 12 Aryl or C6~C 12 Cycloalkyl.

[0028] According to an embodiment of the present application, the halogen is selected from fluorine, bromine or chlorine;

[0029] C1~C 10 The alkyl group is selected from methyl, ethyl, propyl, isopropyl, butyl or tert-butyl;

[0030] C6~C 12 Aryl is selected from phenyl, naphthyl or biphenyl;

[0031] C6~C 12 Cycloalkyl is selected from cyclohexyl or bicyclohexyl;

[0032] The ester group is selected from methyl formate, ethyl formate, butyl formate, methyl sulfonate, ethyl sulfonate or propyl sulfonate;

[0033] j is an integer from 0 to 8;

[0034] One of R5 and R6 is hydrogen, and the other is C1-C6 alkyl;

[0035] One of R7 and R8 is hydrogen, and the other is C1-C4 alkyl

[0036] According to an embodiment of the present application, a lithium acetate group is connected to the main chain of the flexible monomer.

[0037] According to an embodiment of the present application, the flexible monomer has any of the following structures:

[0038]

[0039] According to an embodiment of the present application, the polar monomer has a structure shown in formula (3),

[0040]

[0041] Among them, R9 and R 10 Each is independently selected from -H, -F, -Cl, Br, -I, -CN, -COOR, -SO2OR, substituted or unsubstituted -(CH2) k -CH3;

[0042] R 11 Selected from -H, -F, -Cl, Br, -I, -CN, -COOR, -SO2OR, substituted or unsubstituted -(CH2) p -CH3;

[0043] R 12 Selected from hydrogen, substituted or unsubstituted -(CH2) m -CH3;

[0044] R 13 Selected from substituted or unsubstituted -(CH2) n -;

[0045] R is selected from C1-C6 alkyl;

[0046] k is an integer from 0 to 20;

[0047] p is an integer from 0 to 20;

[0048] m is an integer from 0 to 20;

[0049] n is an integer from 0 to 20;

[0050] The substituted substituent is selected from halogen, ester, C1-C 10 Alkyl, C6~C 12 Aryl or C6~C 12 Cycloalkyl.

[0051] According to an embodiment of the present application, the halogen is selected from fluorine, bromine or chlorine;

[0052] C1~C 10 The alkyl group is selected from methyl, ethyl, propyl, isopropyl, butyl or tert-butyl;

[0053] C6~C 12 Aryl is selected from phenyl, naphthyl or biphenyl;

[0054] C6~C 12 Cycloalkyl is selected from cyclohexyl or bicyclohexyl;

[0055] The ester group is selected from methyl formate, ethyl formate, butyl formate, methyl sulfonate, ethyl sulfonate or propyl sulfonate;

[0056] k is an integer from 0 to 3;

[0057] p is an integer from 3 to 8;

[0058] m is an integer from 1 to 7;

[0059] n is an integer from 0 to 4.

[0060] According to the embodiments of the present application, R9 and R 10 One of them is hydrogen and the other is C1-C3 alkyl;

[0061] R 11 Selected from C3-C7 alkyl;

[0062] R 12 Selected from C1-C6 alkyl;

[0063] R 13 Selected from a bond or a C1-C3 alkyl group.

[0064] According to an embodiment of the present application, a lithium acetate group is connected to the main chain of the polar monomer.

[0065] According to an embodiment of the present application, the polar monomer has a structure as shown in any one of the following:

[0066]

[0067] According to an embodiment of the present application, the structure of the binder polymer is Wherein X is a rigid monomer, Y is a flexible monomer, Z is a polar monomer, and n is an integer of 20 to 500.

[0068] According to an embodiment of the present application, based on the total molar amount of the monomers of the binder polymer, the total molar fraction of the rigid monomer is 10% to 50%.

[0069] According to an embodiment of the present application, based on the total molar amount of the monomers of the binder polymer, the total molar fraction of the flexible monomer is 10% to 50%.

[0070] According to an embodiment of the present application, based on the total molar amount of the monomers of the binder polymer, the total molar fraction of the polar monomers is 40% to 80%.

[0071] According to an embodiment of the present application, based on the total molar amount of monomers of the binder polymer, the sum of the total molar fraction of the rigid monomers and the total molar fraction of the flexible monomers is not less than 20% and not more than 60%.

[0072] According to an embodiment of the present application, the weight average molecular weight of the binder polymer is 50,000 to 600,000, and can be optionally 200,000 to 600,000.

[0073] According to an embodiment of the present application, the viscosity of the binder polymer is 50 cp to 5000 cp.

[0074] According to an embodiment of the present application, the dielectric constant of the binder polymer is 5-12.

[0075] According to an embodiment of the present application, the glass transition temperature of the binder polymer is -50°C to 20°C.

[0076] The second aspect of the present application provides a positive electrode sheet. According to an embodiment of the present application, the positive electrode sheet comprises: a positive electrode active material layer, the positive electrode active material layer comprises: a positive electrode active material, a sulfide solid electrolyte and the binder polymer described in the first aspect.

[0077] According to an embodiment of the present application, based on the total mass of the positive electrode active material layer, the content of the positive electrode active material is 50 wt.% to 85 wt.%.

[0078] According to an embodiment of the present application, based on the total mass of the positive electrode active material layer, the content of the sulfide solid electrolyte is 5 wt.% to 50 wt.%.

[0079] According to an embodiment of the present application, based on the total mass of the positive electrode active material layer, the content of the binder polymer is 0.1 wt.% to 10 wt.%.

[0080] The third aspect of the present application provides a battery. According to an embodiment of the present application, the battery comprises: the positive electrode sheet, the negative electrode sheet and the sulfide solid electrolyte layer described in the second aspect of the present application, wherein the sulfide solid electrolyte layer is located between the positive electrode sheet and the negative electrode sheet.

[0081] According to an embodiment of the present application, the sulfide solid electrolyte layer includes a sulfide solid electrolyte and the binder polymer described in the first aspect.

[0082] The fourth aspect of the present application provides an electric device. According to an embodiment of the present application, the electric device includes the battery described in the third aspect of the present application.

[0083] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0084] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0085] Figure 1 A schematic diagram of the binder polymer structure of one embodiment of the present application is shown;

[0086] Figure 2 A schematic diagram of the method flow of a positive electrode plate according to an embodiment of the present application is shown.

[0087] Reference numerals:

[0088] X: rigid monomer; Y: flexible monomer; Z: polar monomer. DETAILED DESCRIPTION

[0089] The embodiments of the present application are described in detail below. The embodiments described below are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application.

[0090] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of this application, unless otherwise specified, the meaning of "plurality" is two or more.

[0091] The endpoints and any values ​​of the ranges disclosed in this application are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this application.

[0092] In the present application, the terms "include" or "comprising" are open expressions, that is, including the contents specified in the present application, but not excluding other contents.

[0093] At present, the positive electrode binder-solvent system used in traditional liquid batteries is mainly polyvinylidene fluoride (PVDF)-NMP (N-methylpyrrolidone), and the negative electrode binder-solvent system is mainly carboxymethyl cellulose (CMC) / chloroprene rubber (SBR)-water. Since the sulfide solid electrolyte is extremely sensitive to water and polar solvents, the above binder-solvent system cannot meet the wet coating of the sulfide solid-state battery. At present, the binder used in the composite positive electrode sheet (containing positive electrode active materials and sulfide solid electrolyte) of sulfide solid-state batteries is mainly rubber-based polymers, including styrene-butadiene rubber (SBR), nitrile rubber (NBR), polybutadiene rubber (BR), chloroprene rubber (CR), isoprene rubber (IR), etc. Except for styrene-butadiene rubber, the others are all flexible alkane chains with poor dispersibility in the positive electrode and electrolyte, which easily leads to agglomeration. Although styrene-butadiene rubber has a rigid benzene ring group, it is a non-polar polymer, which leads to weak interaction with the main material and cannot provide sufficient bonding force. In addition, the cyano group (-C≡N) on the nitrile rubber chain has a strong bonding ability and is prone to form ion-dipole interaction with lithium ions, reducing the kinetics of lithium ion transmission, thereby affecting the capacity and power performance of the battery. Moreover, due to the solubility of rubber binders, the solvents are mainly benzene solvents such as toluene and xylene. Benzene solvents are highly toxic, have carcinogenic risks, and have certain environmental pollution problems, which poses a safety hazard to personnel in large-scale preparation.

[0094] In view of this, the present application adopts a binder polymer comprising a rigid monomer, a flexible monomer and a polar monomer as the positive electrode sheet of the sulfide solid-state battery. The rigid monomer has a high T g , can effectively disperse the main materials (including positive electrode active materials and sulfide solid electrolytes, etc.), thereby improving the stability of the electrode slurry, the slurry viscosity changes little, and the thixotropy is good; the flexible monomer has a low T g , the binder polymer can be stretched or shrunk well, so that the pole piece has good mechanical properties and processing properties, and can stabilize the electrode slurry to a certain extent, make the particle accumulation more uniform, increase the active specific surface area, and reduce the internal resistance of the battery; the introduction of ester groups in polar monomers can increase the polarity of the binder polymer, improve the interaction between the binder polymer and the main material, and increase the peeling force of the pole piece. In addition, the ester group is stable to the sulfide solid electrolyte, and will continuously undergo complexation and decomplexation reactions with lithium ions under the action of the electric field, which is beneficial to the diffusion of lithium ions. As a result, the mechanical properties and electrochemical properties of the positive electrode can be improved as a whole.

[0095] To this end, the first aspect of the present application proposes a binder polymer. According to an embodiment of the present application, the monomers of the binder polymer include:

[0096] A rigid monomer having at least one of the following substituted or unsubstituted groups: C6 to C 12 Aryl, C3~C 11 Heteroaryl, C4-C8 cycloalkyl or C3-C7 heterocyclic group;

[0097] A flexible monomer having a substituted or unsubstituted C2 to C 30 alkenyl;

[0098] A polar monomer having an ester group.

[0099] Figure 1 The schematic diagram of the structure of the binder polymer according to the embodiment of the present application is shown, X is a rigid monomer, Y is a flexible monomer, and Z is a polar monomer. Figure 1 The advantages of the positive electrode design of this application are elaborated in detail:

[0100] In the positive electrode of the sulfide solid-state battery, by adding a sulfide solid electrolyte to the positive electrode active material layer, the ion transmission efficiency inside the electrode is improved, the polarization during the battery charge and discharge process is reduced, and a more stable interface can be formed between the sulfide solid electrolyte and the positive electrode active material, reducing the interface impedance, which helps to maintain the performance of the battery during long-term cycling. The main materials in the positive electrode active material layer of the liquid battery mainly include the positive electrode active material, while the main materials in the positive electrode active material layer of the solid-state battery mainly include the positive electrode active material and the sulfide solid electrolyte. The addition of the solid phase will require higher dispersion, especially the sulfide solid electrolyte usually has a small particle size and is prone to agglomeration, which will further increase the dispersion requirements.

[0101] To this end, the binder polymer of the present application uses a rigid monomer having an aromatic, heteroaromatic, cycloalkyl or heterocyclic group with given conditions, and the rigid monomer has a relatively high glass transition temperature (T g), can play the role of dispersing the main material, so that the substances are evenly dispersed, avoid agglomeration, improve the stability of the positive electrode slurry, make the viscosity of the positive electrode slurry change little, strong thixotropy, reduce the ion transmission resistance, reduce the internal resistance of the battery, thereby improving the charge and discharge efficiency. In addition, since the sulfide solid electrolyte has low stability and is sensitive to polar solvents and some polar functional groups, the polarity of the above-mentioned rigid groups is very low, and it is not easy to react chemically, thereby improving the stability and ionic conductivity of the sulfide solid electrolyte. In addition, the above-mentioned rigid groups can also enhance the mechanical strength of the binder polymer, thereby resisting the mechanical stress and volume change that may occur in the electrode material during the charge and discharge process. Among them, among the above-mentioned rigid groups, the aromatic group has a better effect, mainly because of its high rigid strength, which helps to better disperse the main material, improve the stability of the positive electrode slurry, make the viscosity of the positive electrode slurry change little, and have strong thixotropy. Moreover, due to its low polarity and low ionic conductivity, it has little effect on the ionic conductivity of the positive electrode active material or the sulfide solid electrolyte, and has better compatibility with the sulfide solid electrolyte, which is conducive to the sulfide solid electrolyte to play a better role.

[0102] The binder polymer of the present application uses a flexible monomer having an olefinic group with given conditions, and the flexible monomer has a low T g , which can make the binder polymer stretch or shrink well, so that the electrode plate has good flexibility and processing performance, and can also stabilize the electrode slurry to a certain extent, make the particles accumulate more evenly, increase the active specific surface area, and reduce the internal resistance of the battery. In addition, the introduction of double bonds can increase the cohesion of the binder polymer and improve its bonding strength, thereby increasing the peeling force of the electrode plate.

[0103] The use of polar monomers with ester groups in the binder polymer of the present application can improve the adhesion between the binder polymer and the electrode active material or current collector, and increase the peeling force of the pole piece; it can also improve the mechanical strength and flexibility of the binder polymer, which helps to resist the volume change during the battery charging and discharging process; it can also reduce the interface impedance between the pole piece and the electrolyte, and improve the ionic conductivity and charging and discharging efficiency. Furthermore, due to the low stability of sulfide solid electrolytes, they are sensitive to polar solvents and some polar functional groups, such as hydroxyl, carboxyl or amino groups. The introduction of ester groups (-COOR) in polar monomers is stable for sulfide solid electrolytes and is not easy to react chemically. Moreover, the ester groups can continuously react with lithium ions under the action of the electric field to form complexes and decomplexes, reduce the interface impedance, and facilitate ion diffusion, thereby improving the capacity and rate performance of the pole piece, and improving the battery charging and discharging efficiency.

[0104] In the present application, the term "aryl" can be a monocyclic, bicyclic or tricyclic carbocyclic ring system, which is an aromatic compound. The term "aryl" can be used interchangeably with the term "aromatic ring", such as an aromatic ring can include phenyl, naphthyl or anthracene. The aryl group can be substituted by a substituent described in the present application. In some embodiments, the number of carbon atoms in the aryl group can be 6, 7, 8, 9, 10, 11 or 12, etc.

[0105] In the present application, the terms "heteroaryl" and "heteroaromatic ring" are used interchangeably, and both refer to an aromatic ring in which one or more atoms are independently and optionally substituted by heteroatoms (heteroatoms are selected from N, O, P, S, where S or P can be independently and optionally substituted by one or more oxygen atoms to obtain groups such as SO, SO2, PO, PO2). In some embodiments, the number of carbon atoms in the heteroaryl group can be 3, 4, 5, 6, 7, 8, 9, 10 or 11, etc.

[0106] In this application, the terms "cycloalkyl" and "carbocycle" are used interchangeably and refer to a monovalent or polyvalent, non-aromatic, saturated or partially unsaturated ring, and do not contain heteroatoms, including monocyclic, bicyclic or tricyclic rings. In some embodiments, the number of carbon atoms in the cycloalkyl group can be 4, 5, 6, 7 or 8, etc.

[0107] In the present application, the terms "heterocyclyl" and "heterocycle" can be used interchangeably, including monocyclic, bicyclic or tricyclic rings, wherein one or more atoms in the ring are independently optionally substituted by heteroatoms (heteroatoms are selected from N, O, P, S, where S or P is independently optionally substituted by one or more oxygen atoms to obtain groups such as SO, SO2, PO, PO2), the ring can be fully saturated or contain one or more unsaturations, but is never aromatic, and the heterocyclic ring system as a whole is not aromatic. In some embodiments, the number of carbon atoms in the heterocycloalkyl group can be 3, 4, 5, 6 or 7, etc.

[0108] In the present application, the term "alkenyl" refers to a carbon atom group having a carbon-carbon double bond (C=C). In some embodiments, the number of carbon atoms in the carbon atom group having an alkenyl group is 2, 4, 5, 8, 10, 12, 15, 18, 20, 22, 25, 28 or 30, etc.

[0109] According to an embodiment of the present application, the rigid monomer has a structure as shown in formula (1),

[0110]

[0111] Wherein, R1 is selected from the following substituted or unsubstituted groups: C6~C 12 Aryl, C3~C 11Heteroaryl, C4-C8 cycloalkyl or C3-C7 heterocyclic group;

[0112] R2, R3 and R4 are each independently selected from -H, -F, -Cl, Br, -I, substituted or unsubstituted -(CH2) i -CH3, i is an integer from 0 to 20;

[0113] The substituted substituent is selected from halogen, ester, C1-C 10 Alkyl or C6~C 12 Cycloalkyl.

[0114] Introducing double bonds in rigid monomers can increase the cohesion of the binder polymer, thereby improving its adhesion. In addition, the above rigid monomers can disperse the main material, improve the stability of the positive electrode slurry, make the viscosity of the positive electrode slurry change little, and have strong thixotropy, which is conducive to the main material to better play its respective role. In addition, the R1, R2, R3 and R4 groups in the rigid monomers are not easy to react chemically with the sulfide solid electrolyte, thereby improving the stability and ionic conductivity of the sulfide solid electrolyte.

[0115] In some embodiments, i is 1, 2, 5, 8, 10, 12, 15, 18, 20, etc.

[0116] According to an embodiment of the present application, R1 is selected from R1' is selected from C1-C4 alkyl, such as methyl, ethyl, propyl or butyl. Bent bonds in structures Refers to the connection site on the molecular structure, that is, substitution The attachment site of R1 in the structure.

[0117] The rigid monomer with the above-mentioned groups can further make the formed binder polymer have greater rigidity, help to better disperse the main material, improve the stability of the positive electrode slurry, make the viscosity of the positive electrode slurry change less, and have strong thixotropy. In addition, since the above-mentioned groups themselves have low polarity, the impact on the ionic conductivity of the positive electrode active material or the sulfide solid electrolyte can be further reduced. At the same time, the above-mentioned groups are more compatible with the sulfide solid electrolyte, avoid reacting with it, and are conducive to the sulfide solid electrolyte to play a better role.

[0118] According to the embodiments of the present application, the C3 to C 11The heteroatoms of the heteroaryl group and the C3-C7 heterocyclic group are each independently selected from O, S or N; the ester group is selected from methyl formate, ethyl formate, butyl formate or sulfonate; i is an integer of 0 to 3. In some embodiments, the sulfonate group is selected from methyl sulfonate, ethyl sulfonate or propyl sulfonate. Thus, the formed binder polymer can further effectively disperse the main material, improve the stability of the positive electrode slurry, make the viscosity of the positive electrode slurry change little, have strong thixotropy, avoid chemical reaction with the sulfide solid electrolyte, improve the stability and ionic conductivity of the sulfide solid electrolyte, and at the same time improve the adhesion of the binder polymer.

[0119] According to an embodiment of the present application, a lithium acetate group is connected to the main chain of the rigid monomer, thereby further improving the ion-conducting ability of the binder polymer.

[0120] According to an embodiment of the present application, the rigid monomer has any of the following structures:

[0121]

[0122] Thus, the formed binder polymer can further effectively disperse the main material, improve the stability of the positive electrode slurry, make the viscosity of the positive electrode slurry change little, have strong thixotropy, avoid chemical reaction with the sulfide solid electrolyte, improve the stability and ionic conductivity of the sulfide solid electrolyte, etc., and at the same time improve the adhesion of the binder polymer.

[0123] According to an embodiment of the present application, the flexible monomer has a structure as shown in formula (2),

[0124]

[0125] Wherein, R5, R6, R7 and R8 are each independently selected from -H, -F, -Cl, Br, -I, -CN, -COOR, -SO2OR, substituted or unsubstituted -(CH2) j -CH3;

[0126] R is selected from C1-C6 alkyl, and C1-C6 alkyl is exemplified as: alkyl with 1, 2, 3, 4, 5, 6 carbon atoms;

[0127] j is an integer from 0 to 20;

[0128] The substituted substituent is selected from halogen, ester, C1-C 10 Alkyl, C6~C 12 Aryl or C6~C 12 Cycloalkyl.

[0129] Therefore, the use of the above-mentioned flexible monomer can further enable the binder polymer to be well stretched or shrunk, so that the electrode plate has further good flexibility and processing performance, and can stabilize the electrode slurry to a certain extent, make the particle accumulation more uniform, increase the active specific surface area, and reduce the internal resistance of the battery. In addition, the above-mentioned groups are highly compatible with sulfide solid electrolytes and are not prone to chemical reactions, thereby improving the stability and ionic conductivity of sulfide solid electrolytes.

[0130] According to an embodiment of the present application, the halogen is selected from fluorine, bromine or chlorine;

[0131] C1~C 10 The alkyl group is selected from methyl, ethyl, propyl, isopropyl, butyl or tert-butyl;

[0132] C6~C 12 Aryl is selected from phenyl, naphthyl or biphenyl;

[0133] C6~C 12 Cycloalkyl is selected from cyclohexyl or bicyclohexyl;

[0134] The ester group is selected from methyl formate, ethyl formate, butyl formate or sulfonate;

[0135] The sulfonate group is selected from methyl sulfonate, ethyl sulfonate or propyl sulfonate;

[0136] j is an integer from 0 to 6, exemplarily 1, 2, 3, 4, 5, 6;

[0137] One of R5 and R6 is hydrogen, and the other is a C1-C6 alkyl group, wherein the C1-C6 alkyl group is exemplified as: an alkyl group having 1, 2, 3, 4, 5, or 6 carbon atoms;

[0138] One of R7 and R8 is hydrogen, and the other is a C1-C4 alkyl group. Examples of the C1-C4 alkyl group include alkyl groups having 1, 2, 3, and 4 carbon atoms.

[0139] Therefore, the use of the above groups can further enable the binder polymer to be well stretched or shrunk, so that the electrode plate has further good flexibility and processing performance. In addition, the above groups are highly compatible with the sulfide solid electrolyte and are not prone to chemical reactions, thereby improving the stability and ion conductivity of the sulfide solid electrolyte.

[0140] According to an embodiment of the present application, a lithium acetate group is connected to the main chain of the flexible monomer, thereby further improving the ion-conducting ability of the binder polymer.

[0141] According to an embodiment of the present application, the flexible monomer has any of the following structures:

[0142]

[0143] Therefore, the use of the above-mentioned flexible monomer can further enable the binder polymer to be well stretched or shrunk, so that the electrode plate has further good flexibility and processing performance. In addition, the above-mentioned group is highly compatible with the sulfide solid electrolyte and is not prone to chemical reaction, thereby improving the stability and ion conductivity of the sulfide solid electrolyte.

[0144] According to an embodiment of the present application, the polar monomer has a structure shown in formula (3),

[0145]

[0146] Among them, R9 and R 10 Each is independently selected from -H, -F, -Cl, Br, -I, -CN, -COOR, -SO2OR, substituted or unsubstituted -(CH2) k -CH3;

[0147] R 11 Selected from -H, -F, -Cl, Br, -I, -CN, -COOR, -SO2OR, substituted or unsubstituted -(CH2) p -CH3;

[0148] R 12 Selected from hydrogen, substituted or unsubstituted -(CH2) m -CH3;

[0149] R 13 Selected from substituted or unsubstituted -(CH2) n -;

[0150] R is selected from C1-C6 alkyl, and C1-C6 alkyl is exemplified as: alkyl with 1, 2, 3, 4, 5, 6 carbon atoms;

[0151] k is an integer from 0 to 20, illustratively 0, 1, 2, 5, 8, 10, 12, 15, 18, 20, etc.;

[0152] p is an integer from 0 to 20, illustratively 0, 1, 2, 5, 8, 10, 12, 15, 18, 20, etc.;

[0153] m is an integer from 0 to 20, illustratively 0, 1, 2, 5, 8, 10, 12, 15, 18, 20, etc.;

[0154] n is an integer of 0 to 20, illustratively 0, 1, 2, 5, 8, 10, 12, 15, 18, 20, etc.;

[0155] The substituted substituent is selected from halogen, a third ester group, a sulfonate group, a C1-C10 Alkyl, C6~C 12 Aryl or C6~C 12 Cycloalkyl.

[0156] Therefore, the use of the above polar monomers can improve the adhesion between the binder polymer and the electrode active material or current collector, increase the pole piece peeling force; it can also improve the mechanical strength and flexibility of the binder polymer, which helps to resist the volume change during the battery charging and discharging process. In addition, the above groups are highly compatible with sulfide solid electrolytes, are not prone to chemical reactions, and improve the stability and ionic conductivity of sulfide solid electrolytes.

[0157] According to an embodiment of the present application, according to an embodiment of the present application, the halogen is selected from fluorine, bromine or chlorine;

[0158] C1~C 10 The alkyl group is selected from methyl, ethyl, propyl, isopropyl, butyl or tert-butyl;

[0159] C6~C 12 Aryl is selected from phenyl, naphthyl or biphenyl;

[0160] C6~C 12 Cycloalkyl is selected from cyclohexyl or bicyclohexyl;

[0161] The ester group is selected from methyl formate, ethyl formate, butyl formate or sulfonate, and exemplarily, the sulfonate group is selected from methyl sulfonate, ethyl sulfonate or propyl sulfonate;

[0162] k is an integer from 0 to 3, illustratively 0, 1, 2 or 3;

[0163] p is an integer from 3 to 8, illustratively 3, 4, 5, 6, 7, 8, etc.;

[0164] m is an integer from 1 to 7, illustratively 1, 2, 3, 4, 5, 6, 7, etc.;

[0165] n is an integer of 0 to 4, and illustratively is 0, 1, 2, 3, 4, and the like.

[0166] According to the embodiments of the present application, R9 and R 10 One of them is hydrogen and the other is C1-C3 alkyl;

[0167] R 11 Selected from C3-C7 alkyl;

[0168] R 12 Selected from C1-C6 alkyl;

[0169] R 13 Selected from a bond or a C1-C3 alkyl group.

[0170] Therefore, the use of the above groups can further improve the adhesion between the binder polymer and the electrode active material or the current collector, increase the electrode peeling force, especially R 11 The long-chain alkyl group is selected to increase the degree of branching, which is conducive to weak interactions between long-chain branches, such as dipole effects and van der Waals forces, increasing adhesion; it can also further improve the mechanical strength and flexibility of the binder polymer, which helps to resist volume changes during battery charging and discharging. In addition, the above-mentioned groups are highly compatible with sulfide solid electrolytes and are not prone to chemical reactions, further improving the stability and ionic conductivity of sulfide solid electrolytes.

[0171] According to an embodiment of the present application, a lithium acetate group is connected to the main chain of the polar monomer, thereby improving the ion-conducting ability of the binder polymer.

[0172] According to an embodiment of the present application, the polar monomer has a structure as shown in any one of the following:

[0173]

[0174] Therefore, the use of the above polar monomers can further improve the adhesion between the binder polymer and the electrode active material or current collector, increase the pole piece peeling force; it can also further improve the mechanical strength and flexibility of the binder polymer, which helps to resist the volume change during the battery charging and discharging process. In addition, the above groups are highly compatible with sulfide solid electrolytes and are not prone to chemical reactions, further improving the stability and ionic conductivity of sulfide solid electrolytes.

[0175] According to an embodiment of the present application, the structure of the binder polymer is Wherein X is a rigid monomer, Y is a flexible monomer, Z is a polar monomer, and n is an integer of 20 to 500.

[0176] It should be noted that the structure inside “[]” in the above structure is the repeating unit of the binder polymer, for example, It means n XYZXYZXYZ are connected.

[0177] The binder polymer with the above arrangement further has better flexibility, mechanical strength and dispersibility, etc., which is conducive to ion diffusion and improves the performance of the positive electrode. Among them, the double bonds of any two monomers can be used as cross-linking points to form a three-dimensional network structure by reacting with the double bonds of other molecules. Exemplarily, n can be 2, 3, 4, 5, 6, 7, 8, 9, etc.

[0178] According to an embodiment of the present application, based on the total molar amount of the monomers of the binder polymer, the molar fraction of the rigid monomer is 10% to 50%. As a result, the mechanical strength and dispersibility of the binder polymer are strong, the positive electrode slurry has good stability, and it is not easy to agglomerate, so that the viscosity of the positive electrode slurry changes little and the thixotropy is strong. In addition, the binder polymer has good flexibility and processing performance, and the interface impedance between the positive electrode sheet and the sulfide solid electrolyte is low, which is conducive to ion and electron transmission. Exemplarily, based on the total molar amount of the monomers of the binder polymer, the molar fraction of the rigid monomer can be 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, etc.

[0179] According to an embodiment of the present application, based on the total molar amount of the monomers of the binder polymer, the molar fraction of the flexible monomer is 10% to 50%. As a result, the binder polymer has good flexibility and processing performance, and has good mechanical strength. Exemplarily, based on the total molar amount of the monomers of the binder polymer, the molar fraction of the flexible monomer can be 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, etc.

[0180] According to an embodiment of the present application, based on the total molar amount of the monomers of the binder polymer, the molar fraction of the polar monomer is 40% to 80%. As a result, the binder polymer has strong adhesion and good mechanical strength and flexibility. The interface impedance between the positive electrode plate and the sulfide solid electrolyte is low, which is conducive to ion and electron transmission. Exemplarily, the molar fraction of the polar monomer can be 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, etc.

[0181] According to an embodiment of the present application, based on the total molar amount of the monomers of the binder polymer, the sum of the molar fraction of the rigid monomer and the molar fraction of the flexible monomer is not less than 20% and not more than 60%. As a result, the binder polymer can have good mechanical strength, flexibility, dispersibility and adhesion, etc. The interface impedance between the positive electrode plate and the sulfide solid electrolyte is low, which is conducive to ion and electron transmission, and the overall performance of the positive electrode plate is improved. Exemplarily, based on the total molar amount of the monomers of the binder polymer, the sum of the molar fraction of the rigid monomer and the molar fraction of the flexible monomer is 20%, 30%, 40%, 50%, 60%, etc.

[0182] According to an embodiment of the present application, the weight average molecular weight of the binder polymer is 50,000 to 600,000. In some embodiments, the weight average molecular weight of the binder polymer is 200,000 to 600,000. As a result, the binder polymer can have good mechanical strength, flexibility, dispersibility and adhesion, etc. The interface impedance between the positive electrode sheet and the sulfide solid electrolyte is low, which is conducive to ion and electron transmission, and the overall performance of the positive electrode sheet is improved. Exemplarily, the weight average molecular weight of the binder polymer is 50,000, 100,000, 200,000, 300,000, 400,000, 500,000, 600,000, etc.

[0183] According to an embodiment of the present application, the viscosity of the binder polymer is 50cp to 5000cp. The viscosity can be measured in combination with a viscometer. The binder polymer having the above viscosity has better viscosity, better flexibility, mechanical strength and dispersibility, strong stability of the positive electrode slurry, uniform dispersion, not easy to agglomerate, small thixotropy, conducive to ion and electron transport, low internal resistance, excellent processing performance, and easy coating. Exemplarily, the viscosity of the binder polymer is 50cp, 100cp, 500cp, 1000cp, 1500cp, 2000cp, 2500cp, 3000cp, 3500cp, 4000cp, 4500cp, 5000cp.

[0184] According to an embodiment of the present application, the dielectric constant of the binder polymer is 5 to 12. The dielectric constant can be measured in combination with a dielectric constant measuring instrument. As a result, the binder polymer has strong adhesion to the electrode active material, which prevents the electrode active material from falling off during the charge and discharge process, and is conducive to the uniform embedding and extraction of ions, and the battery has strong charge and discharge performance and cycle stability. Exemplarily, the dielectric constant is 5, 6, 7, 8, 9, 10, 11 or 12.

[0185] According to an embodiment of the present application, the glass transition temperature (T g ) is -50℃~20℃. The glass transition temperature (T g ) is a temperature parameter that measures the change of the binder polymer from a hard and glassy state to a soft and rubbery state, and can be measured by combining a differential scanning calorimeter, a thermomechanical analyzer, a dynamic thermomechanical analyzer, a dilatometer, a refractometer, a nuclear magnetic resonance spectrometer, a thermogravimetric analyzer, a rheometer, etc. g The binder polymer has good flexibility and mechanical strength, strong adhesion, dispersibility and stability, so that the positive electrode has good electrode peeling force, processing performance and electrochemical performance. g It is -50℃, -40℃, -30℃, -20℃, -10℃, 0℃, 10℃, 20℃, etc.

[0186] According to an embodiment of the present application, the method for preparing the binder polymer of the present application includes:

[0187] The rigid monomer, the flexible monomer and the polar monomer are prepared into a hydrocarbon phase liquid, placed in a polymerization kettle, and a catalyst, a molecular weight regulator, a terminator, etc. are added. The reaction time is controlled at 1-48 hours, and the polymerization temperature is 120°C to 180°C. When the polymerization conversion rate reaches more than 60%, a terminator is added to terminate the polymerization reaction, and the polymer is dried to obtain a binder polymer. Furthermore, after the polymerization reaction is terminated, the unreacted monomer can be recovered by processes such as high-temperature degassing. Anti-aging agents and polymer coagulants can be added to the binder polymer to further improve the stability, durability, dispersibility, etc. of the binder polymer, and improve the adhesion and processing properties.

[0188] The second aspect of the present application proposes a positive electrode plate. According to an embodiment of the present application, the positive electrode plate includes: a positive electrode active material layer, and the positive electrode active material layer includes: a positive electrode active material, a sulfide solid electrolyte and the binder polymer described in the first aspect. The binder polymer of the present application takes into account good adhesion, flexibility and dispersibility, is conducive to the transmission of ions and electrons, and makes the positive electrode plate have excellent mechanical properties, processing properties and electrochemical properties. The characteristics and advantages described above for the binder polymer are also applicable to the positive electrode plate, and will not be repeated here.

[0189] According to an embodiment of the present application, based on the total mass of the positive electrode active material layer, the content of the positive electrode active material is 50wt.% to 85wt.%. Thus, it has better electrochemical properties, including high specific capacity, good charge and discharge efficiency, and excellent cycle stability. Exemplarily, based on the total mass of the positive electrode active material layer, the content of the positive electrode active material is 50wt.%, 60wt.%, 70wt.%, 80wt.%, 85wt.%, etc.

[0190] According to an embodiment of the present application, based on the total mass of the positive electrode active material layer, the content of the sulfide solid electrolyte is 5wt.% to 50wt.%. As a result, the charge and discharge efficiency, power density, chemical stability and cycle efficiency of the battery can be improved, the interface impedance can be reduced, and the stability of the pole piece structure can be improved to resist the volume change during the charge and discharge process of the battery. Exemplarily, based on the total mass of the positive electrode active material layer, the content of the sulfide solid electrolyte is 5wt.%, 10wt.%, 20wt.%, 30wt.%, 40wt.%, 50wt.%, etc.

[0191] According to an embodiment of the present application, based on the total mass of the positive electrode active material layer, the content of the binder polymer is 0.1wt.% to 10wt.%. Thus, the peeling force, processing performance and electrochemical performance of the positive electrode sheet can be improved. Exemplarily, based on the total mass of the positive electrode active material layer, the content of the binder polymer is 0.1wt.%, 1wt.%, 2wt.%, 5wt.%, 8wt.%, 10wt.%, etc.

[0192] According to an embodiment of the present application, the positive electrode active material may include LiFe 1-x’ M' x’ PO4、LiMn 2-y’ M y’ O4 and LiNi x Co y Mn z M 1-x-y-z O2, wherein M' includes one or more of Mn, Mg, Co, Ni, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, V or Ti, M includes one or more of Fe, Co, Ni, Mn, Mg, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, V or Ti, and 0≤x'<1, 0≤y'≤1, 0≤y≤1, 0≤x≤1, 0≤z≤1, x+y+z≤1.

[0193] As an example, the positive electrode active material may include LiCoO2, LiFePO4, LiFe 0.8 Mn 0.2 PO4, LiMn2O4, LiNi 0.5 Co 0.2 Mn 0.3 O2、LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.5 Co 0.2 Mn 0.2 Al 0.1 O2、LiNi 0.5 Co 0.2 Al 0.3 One or more of O2.

[0194] According to an embodiment of the present application, the positive electrode active material includes Na c P d (W a O b )Z e, wherein P includes a transition metal element, W includes at least one of phosphorus, sulfur, silicon, and tungsten, z includes F atoms, 0≤c≤10, 0≤d≤5, 0≤a≤10, 0≤b≤10, and 0≤e≤5.

[0195] As an example, the positive electrode active material includes at least one of NaFePO4, Na2FeP2O7, Na4Fe3(PO4)2P2O7, Na3V2(PO4)3, and Na2Fe(SO4)2.

[0196] According to the embodiments of the present application, the sulfide solid electrolyte includes a glassy or glass-ceramic Li-PS system, a sulfur-silver-germanium Li6PS5X (LPSC) system, a lithium-germanium-phosphorus-sulfur Li 10 GeP2S 12 (LGPS) system or systems.

[0197] According to an embodiment of the present application, the positive electrode plate further includes a current collector, and the positive electrode active material layer is located on one side of the current collector.

[0198] According to an embodiment of the present application, the positive electrode active material layer further includes a conductive material, and the conductive material is a common conductive agent for positive electrodes, such as acetylene black, carbon nanotubes, carbon fibers, carbon black, and the like.

[0199] In addition, the present application also proposes a method for preparing the positive electrode sheet described in the second aspect. According to the embodiments of the present application, see Figure 2 , the method comprising:

[0200] S100 Hybrid

[0201] According to the embodiment of the present application, the positive electrode active material, the sulfide solid electrolyte, the binder polymer and the solvent are mixed to obtain the positive electrode slurry, thereby forming a uniform positive electrode slurry that is not prone to agglomeration.

[0202] According to an embodiment of the present application, the solvent includes an ester solvent. Since the binder polymer contains an ester group, the binder polymer can have good solubility in the ester solvent, avoid benzene solvents, reduce toxicity and use safety, and be environmentally friendly.

[0203] According to an embodiment of the present application, the ester solvent includes one or more of diethyl carbonate, butyl carbonate, ethyl methyl carbonate, butyl acetate, butyl butyrate and methyl benzoate, thereby effectively dissolving the positive electrode active material, the sulfide solid electrolyte and the binder polymer.

[0204] According to an embodiment of the present application, the solid content of the positive electrode slurry is 30wt.% to 90wt.%. As a result, the positive electrode slurry has strong uniformity, stability and rheology, which is conducive to the production of high-performance batteries. Exemplarily, it is 40wt.%, 50wt.%, 60wt.%, 70wt.%, 80wt.%, etc.

[0205] S200 gets the positive electrode

[0206] According to an embodiment of the present application, the positive electrode slurry is applied to at least one side surface of a positive electrode current collector to obtain a positive electrode sheet. Exemplarily, the positive electrode sheet can be obtained by wet coating on the current collector.

[0207] It should be noted that the features and advantages described above for the positive electrode plate in the first aspect are also applicable to this method and will not be repeated here.

[0208] The third aspect of the present application proposes a battery. According to an embodiment of the present application, the battery comprises: the positive electrode sheet, the negative electrode sheet and the sulfide solid electrolyte layer described in the second aspect of the present application, and the sulfide solid electrolyte layer is located between the positive electrode sheet and the negative electrode sheet. As a result, the battery of the present application has excellent electrochemical properties. Exemplarily, the battery of the present application can be a solid-state battery, a semi-solid-state battery or a liquid battery.

[0209] According to an embodiment of the present application, the sulfide solid electrolyte layer includes a sulfide solid electrolyte and the binder polymer described in the first aspect. The features and advantages described for the binder polymer described in the first aspect are also applicable to the binder polymer in the sulfide solid electrolyte layer, and will not be repeated here.

[0210] According to the embodiments of the present application, a sulfide solid electrolyte layer may be coated, dry extruded, stacked or transferred on the positive electrode sheet.

[0211] According to an embodiment of the present application, the negative electrode sheet is selected from a lithium copper composite foil or a copper foil / stainless steel foil attached with a lithium alloy negative electrode, and the lithium alloy negative electrode is selected from a lithium indium alloy, a lithium silicon alloy, a lithium boron alloy, a lithium tin alloy, a lithium magnesium alloy, a lithium aluminum alloy, a lithium silver alloy, etc. Exemplarily, the negative electrode sheet can be applied to the side of the sulfide solid electrolyte layer away from the positive electrode sheet by pressing or the like to obtain a battery.

[0212] The battery of the present application may include a battery cell form, a battery module form and a battery pack form. In some embodiments, the battery cells can be assembled into a battery module, and the number of battery cells contained in the battery module can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery module. In some embodiments, the battery modules can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery pack.

[0213] It should be noted that the features and advantages described above for the positive electrode plate in the first aspect are also applicable to this battery and will not be repeated here.

[0214] The fourth aspect of the present application provides an electrical device, wherein the electrical device comprises the battery described in the third aspect of the present application. Therefore, the electrical device of the present application has excellent electrochemical performance.

[0215] Battery cells, battery modules, and battery packs can be used as power sources for electrical devices or as energy storage units for electrical devices. Electrical devices may include, but are not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships, satellites, energy storage systems, etc.

[0216] As an electrical device, a battery cell, battery module or battery pack can be selected according to its usage requirements.

[0217] As an embodiment, the electric device may be a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, etc. In order to meet the requirements of the electric device for high power and high energy density of the battery, a battery pack or a battery module may be used.

[0218] As another embodiment, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and a battery cell may be used as a power source.

[0219] It should be noted that the features and advantages described above for the battery in the third aspect of the present application are also applicable to the electrical equipment in the fourth aspect of the present application and will not be repeated here.

[0220] The scheme of the present application will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the literature in this area or the product specification are carried out. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained commercially.

[0221] Example 1

[0222] Sulfide all-solid-state battery composite positive electrode slurry, pole piece and battery preparation steps:

[0223] All the following steps are completed in a drying room with a dew point below -50°C.

[0224] Step 1: Provide a binder polymer, wherein the rigid monomer X of the binder polymer is The flexible monomer Y is The polar monomer Z is The binder polymer structure is n is 343. Based on the total molar amount of the monomers of the binder polymer, the molar fraction of the rigid monomer is 30%, the molar fraction of the flexible monomer is 30%, and the molar fraction of the polar monomer is 40%. The weight average molecular weight of the binder polymer is 400,000, the dielectric constant is 8, and the glass transition temperature T g The temperature is 5°C and the viscosity is 600cp.

[0225] The steps for preparing the binder polymer are as follows:

[0226] Into an adiabatic reactor (equipped with a stirring device), a rigid monomer, a flexible monomer and a polar monomer (molar ratio of 0.3:0.3:0.4), 0.1% of the main catalyst cyclopentadienamide (based on the total mass of the three monomers), and 0.2% of the co-catalyst methylaluminoxane (based on the total mass of the three monomers) were added. The polymerization temperature was 150°C, the time was 8 hours, and the reaction pressure was 70 bar. During the reaction, hydrogen was introduced as a molecular weight regulator at a flow rate of 100 ml / min and the ventilation time was 30 minutes. After the polymerization was completed, 100 g of deactivator water was added to the adiabatic reactor, the feed liquid was collected, and put into a distillation tower, and reacted at 120°C for 2 hours to obtain a binder polymer.

[0227] Step 2: Add 75g of NCM811 positive electrode material, 20g of solid electrolyte Li6PS5Cl, 3g of the above-mentioned binder polymer, and 2g of acetylene black to 100g of butyl butyrate solvent, and then stir in a vacuum mixer to form a stable and uniform positive electrode slurry. The positive electrode slurry is uniformly and intermittently coated on both sides of the carbon-coated aluminum foil (aluminum foil size: width 160mm, thickness 16μm), then dried at 373K, and a composite positive electrode layer is obtained after roller pressing. The positive electrode material content in the composite positive electrode layer is 75wt.%, the solid electrolyte content is 20%, the binder polymer content is 3wt.%, and the acetylene black content is 2%.

[0228] Step 3: 58.2 g of Li6PS5Cl and 1.8 g of the above-mentioned binder polymer were placed in 60 g of butyl butyrate solution and stirred thoroughly to form a stable and uniform electrolyte slurry. The electrolyte slurry was continuously coated on the composite positive electrode layer, and then dried at 373 K to control the coating layer thickness to 50 μm to obtain an electrolyte layer-composite positive electrode layer.

[0229] Step 4: Cut the electrolyte layer-composite positive electrode layer into a membrane sheet with a size of 21 mm×41 mm.

[0230] Step 5: Select lithium copper composite foil as the negative electrode layer, the lithium layer thickness is 15 μm, and cut it into 20 mm × 40 mm membrane sheets.

[0231] Step 6: Align the electrolyte layer-composite positive electrode layer membrane obtained in step 3 and the negative electrode layer obtained in step 4 and place them in a hot press, hot press at 453K for 1 hour and a pressure of 200 MPa, and then take out the sample after vacuum sealing with an aluminum plastic film. Finally, the pressed sample is pressed in an isostatic press at 200 MPa for 300 seconds to obtain the battery of this embodiment.

[0232] Example 2

[0233] The difference from Example 1 is that in step 1, the rigid monomer X of the binder polymer is The flexible monomer Y is The polar monomer Z is The binder polymer structure is n is 343. Based on the total molar amount of the monomers of the binder polymer, the molar fraction of the rigid monomer is 30%, the molar fraction of the flexible monomer is 30%, and the molar fraction of the polar monomer is 40%. The weight average molecular weight of the binder polymer is 400,000, the dielectric constant is 8, and the glass transition temperature T g The temperature is 5°C and the viscosity is 800cp.

[0234] The method for preparing the binder polymer is similar to that of Example 1, except that the rigid monomer, the flexible monomer and the polar monomer are of different types.

[0235] Example 3

[0236] The difference from Example 1 is that in step 1, the rigid monomer X of the binder polymer is The flexible monomer Y is The polar monomer Z is The binder polymer structure is n is 343. Based on the total molar amount of the monomers of the binder polymer, the molar fraction of the rigid monomer is 30%, the molar fraction of the flexible monomer is 30%, and the molar fraction of the polar monomer is 40%. The weight average molecular weight of the binder polymer is 400,000, the dielectric constant is 8, and the glass transition temperature T g The temperature is 5°C and the viscosity is 700cp.

[0237] Example 4

[0238] The difference from Example 1 is that in step 1, the rigid monomer X of the binder polymer is The flexible monomer Y is The polar monomer Z is The binder polymer structure is n is 343. Based on the total molar amount of the monomers of the binder polymer, the molar fraction of the rigid monomer is 30%, the molar fraction of the flexible monomer is 30%, and the molar fraction of the polar monomer is 40%. The weight average molecular weight of the binder polymer is 400,000, the dielectric constant is 8, and the glass transition temperature T g The temperature is 5°C and the viscosity is 700cp.

[0239] Example 5

[0240] The difference from Example 1 is that in step 1, the rigid monomer X of the binder polymer is The flexible monomer Y and the polar monomer Z are the same as those in Example 1, and the binder polymer structure is n is 343. Based on the total molar amount of the monomers of the binder polymer, the molar fraction of the rigid monomer is 30%, the molar fraction of the flexible monomer is 30%, and the molar fraction of the polar monomer is 40%. The weight average molecular weight of the binder polymer is 400,000, the dielectric constant is 8, and the glass transition temperature T g The temperature is 0℃ and the viscosity is 600cp.

[0241] Example 6

[0242] The difference from Example 1 is that the polar monomer Z is

[0243] Example 7

[0244] The difference from Example 1 is that in step 1, the polar monomer Z is

[0245] Example 8

[0246] The difference from Example 1 is that in step 1, the binder polymer structure is n is 343.

[0247] In the step of preparing the binder polymer, the polymerization temperature was 180°C.

[0248] Example 9

[0249] The difference from Example 1 is that in step 1, the binder polymer structure is n is 343.

[0250] In the step of preparing the binder polymer, the polymerization temperature was 120°C.

[0251] Example 10

[0252] The difference from Example 1 is that in step 1, based on the total molar amount of the monomers of the binder polymer, the molar fraction of the rigid monomer is 25%, the molar fraction of the flexible monomer is 25%, and the molar fraction of the polar monomer is 50%. The weight average molecular weight of the binder polymer is 400,000, the dielectric constant is 11, and the glass transition temperature T g The temperature is 5°C and the viscosity is 700cp.

[0253] Embodiment 11

[0254] The difference from Example 1 is that in step 1, based on the total molar amount of the monomers of the binder polymer, the molar fraction of the rigid monomer is 20%, the molar fraction of the flexible monomer is 20%, and the molar fraction of the polar monomer is 60%. The weight average molecular weight of the binder polymer is 400,000, the dielectric constant is 11, and the glass transition temperature T g The temperature is 5°C and the viscosity is 750cp.

[0255] Example 12

[0256] The difference from Example 1 is that in step 1, based on the total molar amount of the monomers of the binder polymer, the molar fraction of the rigid monomer is 15%, the molar fraction of the flexible monomer is 15%, and the molar fraction of the polar monomer is 70%. The weight average molecular weight of the binder polymer is 400,000, the dielectric constant is 12, and the glass transition temperature T g The temperature is 5°C and the viscosity is 800cp.

[0257] Example 13

[0258] The difference from Example 1 is that in step 1, based on the total molar amount of the monomers of the binder polymer, the molar fraction of the rigid monomer is 10%, the molar fraction of the flexible monomer is 10%, and the molar fraction of the polar monomer is 80%. The weight average molecular weight of the binder polymer is 400,000, the dielectric constant is 12.5, and the glass transition temperature T g The temperature is 5°C and the viscosity is 850cp.

[0259] Embodiment 14

[0260] The difference from Example 1 is that in step 1, the rigid monomer X of the binder polymer is

[0261] Embodiment 15

[0262] The difference from Example 1 is that in step 1, the rigid monomer X of the binder polymer is

[0263] Example 16

[0264] The difference from Example 1 is that in step 1, the rigid monomer X of the binder polymer is

[0265] Embodiment 17

[0266] The difference from Example 1 is that in step 1, based on the total molar amount of the monomers of the binder polymer, the molar fraction of the rigid monomer is 60%, the molar fraction of the flexible monomer is 30%, and the molar fraction of the polar monomer is 10%. The weight average molecular weight of the binder polymer is 400,000, the dielectric constant is 8, and the glass transition temperature T g The temperature is -5°C and the viscosity is 400cp.

[0267] Embodiment 18

[0268] The difference from Example 1 is that in step 1, based on the total molar amount of the monomers of the binder polymer, the molar fraction of the rigid monomer is 5%, the molar fraction of the flexible monomer is 5%, and the molar fraction of the polar monomer is 90%. The weight average molecular weight of the binder polymer is 400,000, the dielectric constant is 8, and the glass transition temperature T g The temperature is 5°C and the viscosity is 600cp.

[0269] Comparative Example 1

[0270] The difference from Example 1 is that in step 1, the binder polymer used is nitrile rubber (polymerized from butadiene and acrylonitrile, with acrylonitrile molar fraction of 20%), with a molecular weight of 400,000, a dielectric constant of 12, and a glass transition temperature T g The temperature is -35℃ and the viscosity is 800cp.

[0271] In step 2, butyl butyrate is replaced by xylene.

[0272] Comparative Example 2

[0273] The difference from Example 1 is that in step 1, the binder polymer does not contain a rigid monomer, and based on the total molar amount of the monomers of the binder polymer, the molar fraction of the flexible monomer is 50%, and the molar fraction of the polar monomer is 50%. The molecular weight of the binder polymer is 400,000, the dielectric constant is 8, and the glass transition temperature T g The temperature is 15°C and the viscosity is 600cp.

[0274] Comparative Example 3

[0275] The difference from Example 1 is that in step 1, the binder polymer does not contain a flexible monomer, and based on the total molar amount of the monomers of the binder polymer, the molar fraction of the rigid monomer is 50%, and the molar fraction of the polar monomer is 50%. The molecular weight of the binder polymer is 400,000, the dielectric constant is 8, and the glass transition temperature T g The temperature is 0℃ and the viscosity is 600cp.

[0276] Comparative Example 4

[0277] The difference from Example 1 is that in step 1, the binder polymer does not contain polar monomers, and based on the total molar amount of the monomers of the binder polymer, the molar fraction of the rigid monomer is 50%, and the molar fraction of the flexible monomer is 50%. The molecular weight of the binder polymer is 400,000, the dielectric constant is 8, and the glass transition temperature T g The temperature is 5°C and the viscosity is 600cp.

[0278] Comparative Example 5

[0279] The difference from Example 1 is that in step 1, the rigid monomer of the binder polymer is ethylene.

[0280] Comparative Example 6

[0281] The difference from Example 1 is that in step 1, the polar monomer of the binder polymer is acrylonitrile.

[0282] Test Case

[0283] The all-solid-state lithium batteries obtained in Examples 1-18 and Comparative Examples 1-6 were tested for capacity and rate charging performance, and the test method was as follows:

[0284] 1. Take 5 batteries prepared in each embodiment and comparative example, and test the battery charge and discharge capacity at 0.1C on a LAND CT 2001C secondary battery performance tester at 298±1K. The steps are as follows: leave for 10 minutes; charge at a constant current until 4.2V is cut off; leave for 10 minutes, then discharge at a constant current until 2.6V, and the first cycle discharge specific capacity is the capacity of the battery.

[0285] Repeat this step and continue to cycle at 0.1C. After that, the battery is further tested for rate charging performance using different rates of 0.5C charging and constant current discharge (0.1C), and characterized by 0.5C charging specific capacity. The electrochemical workstation EIS is used to record the AC impedance of the battery at 100% SOC, in the frequency range of 1kH Z The resistance values ​​on the left and right sides are analyzed, and the average value of each group is taken as the charge transfer impedance of the composite positive electrode.

[0286] 2. The positive electrode slurry stability test and the electrode stripping force test methods are as follows:

[0287] Stability test: Take 5 ml of positive electrode slurry and place it on the sample stage of the rheometer (RHEOPLUS / 32). Set the distance d from the test plate to the sample stage to 0.5 mm. Test 44 points. The test time for each point is 5 seconds. The shear force range is 0.1 seconds. -1 -2000s -1 The thixotropy calculation formula of the positive electrode slurry is as follows: 100% - slurry viscosity (50s -1 ) / Slurry viscosity (1s -1 )×100% of the positive electrode slurry viscosity.

[0288] Pole piece peeling force test: Cut the prepared positive electrode piece to a suitable length, stick tape on the surface, cut it into a size of 40×110mm with a cutter, and place it on a universal stretching machine for a peeling force test.

[0289] The results are shown in Table 1. Compared with Comparative Examples 1-6, Examples 1-18 have better battery performance, slurry thixotropic properties and electrode stripping properties.

[0290] Compared with Comparative Example 1, Example 1 uses nitrile rubber as the binder polymer. Since the acrylonitrile component of the nitrile rubber binder forms an ion-dipole effect with the electrolyte, it hinders ion transmission during the battery charge and discharge process, resulting in increased battery impedance and high thixotropy of the slurry. However, the binder polymer of the present application has no such interaction with the electrolyte and has a lower impedance.

[0291] Compared with Comparative Example 2, the addition of a rigid monomer in Example 1 can play a dispersing role, improve the stability of the positive electrode slurry, have appropriate thixotropy, reduce the ion transmission resistance, reduce the internal resistance of the battery, and thus improve the charging efficiency.

[0292] Compared with comparative example 3, the addition of flexible monomers in embodiment 1 can stabilize the slurry to a certain extent, make the particle accumulation more uniform, increase the active specific surface area, and reduce the internal resistance of the battery. In addition, the introduction of double bonds can increase the cohesion of the binder polymer and improve its bonding strength, thereby increasing the peeling force of the pole piece.

[0293] Compared with Comparative Example 4, the addition of polar monomers in Example 1 can improve the adhesion of the binder polymer, increase the electrode peeling force, and improve the thixotropy of the positive electrode slurry; it can also reduce the interface impedance between the electrode and the electrolyte, and improve the ionic conductivity and charge and discharge efficiency.

[0294] Compared with Comparative Example 5, Example 1 uses an aryl, heteroaryl, cycloalkyl or heterocyclic group as a rigid monomer, which can improve the rigid strength, help to better disperse the main material, improve the stability of the positive electrode slurry, make the viscosity of the positive electrode slurry change less, and have appropriate thixotropy, reduce the interface impedance between the pole piece and the electrolyte, and improve the charge and discharge efficiency. In addition, the aromatic group itself has a low polarity, which can further reduce the impact on the ionic conductivity of the positive electrode active material or the sulfide solid electrolyte.

[0295] Compared with Example 6, Example 1 has a 11 Selecting long-chain alkyl (C5 alkyl) can increase the degree of branching, which is conducive to weak interactions between long-chain branches, such as dipole action and van der Waals force, increasing adhesion, thereby improving thixotropy of the slurry and electrode peeling force. However, compared with short-chain alkyl, the internal resistance of batteries made with long-chain alkyl is slightly higher and the charge and discharge performance is slightly lower. In general, long-chain alkyl is preferred.

[0296] Compared with Example 7, in Example 1, a lithium acetate group is connected to the main chain of the polar monomer, which can improve the ion conductivity of the binder polymer, thereby improving the charge and discharge performance of the battery.

[0297] Table 1 Capacity and rate charging performance of all-solid-state lithium batteries and characteristics of positive electrode slurry

[0298]

[0299]

[0300] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A binder polymer, characterized in that The monomers of the binder polymer include: A rigid monomer having at least one of the following substituted or unsubstituted groups: C6 to C 12 Aryl, C3~C 11 Heteroaryl, C4-C8 cycloalkyl or C3-C7 heterocyclic group; A flexible monomer having a substituted or unsubstituted C2 to C 30 alkenyl; A polar monomer having an ester group.

2. The binder polymer according to claim 1, characterized in that The rigid monomer has a structure shown in formula (1), Wherein, R1 is selected from the following substituted or unsubstituted groups: C6~C 12 Aryl, C3~C 11 Heteroaryl, C4-C8 cycloalkyl or C3-C7 heterocyclic group; R2, R3 and R4 are each independently selected from -H, -F, -Cl, Br, -I, substituted or unsubstituted -(CH2) i -CH3, i is an integer from 0 to 20; The substituted substituent is selected from halogen, ester, C1-C 10 Alkyl or C6~C 12 Cycloalkyl.

3. The binder polymer according to claim 2, characterized in that R1 is selected from R1' is selected from C1-C4 alkyl; C3~C 11 The heteroatoms of the heteroaryl group and the C3-C7 heterocyclic group are each independently selected from O, S or N; The ester group is selected from methyl formate, ethyl formate, butyl formate or sulfonate; i is an integer from 0 to 3.

4. The binder polymer according to claim 3, characterized in that The sulfonate group is selected from methyl sulfonate, ethyl sulfonate or propyl sulfonate.

5. The binder polymer according to any one of claims 1 to 4, characterized in that A lithium acetate group is connected to the main chain of the rigid monomer.

6. The binder polymer according to claim 1, characterized in that The rigid monomer has a structure shown in any of the following:

7. The binder polymer according to claim 1, characterized in that The flexible monomer has a structure shown in formula (2), Wherein, R5, R6, R7 and R8 are each independently selected from -H, -F, -Cl, Br, -I, -CN, -COOR, -SO2OR, substituted or unsubstituted -(CH2) j -CH3; R is selected from C1-C6 alkyl; j is an integer from 0 to 20; The substituted substituent is selected from halogen, ester, C1-C 10 Alkyl, C6~C 12 Aryl or C6~C 12 Cycloalkyl.

8. The binder polymer according to claim 7, characterized in that The halogen is selected from fluorine, bromine or chlorine; C1~C 10 The alkyl group is selected from methyl, ethyl, propyl, isopropyl, butyl or tert-butyl; The C6~C 12 Aryl is selected from phenyl, naphthyl or biphenyl; C6~C 12 Cycloalkyl is selected from cyclohexyl or bicyclohexyl; The ester group is selected from methyl formate, ethyl formate, butyl formate or sulfonate; j is an integer from 0 to 6; One of R5 and R6 is hydrogen, and the other is C1-C6 alkyl; One of R7 and R8 is hydrogen, and the other is C1-C4 alkyl.

9. The binder polymer according to claim 8, characterized in that The sulfonate group is selected from methyl sulfonate, ethyl sulfonate or propyl sulfonate.

10. The binder polymer according to any one of claims 1, 7 to 9, characterized in that: A lithium acetate group is connected to the main chain of the flexible monomer.

11. The binder polymer according to claim 1, characterized in that The flexible monomer has any of the following structures:

12. The binder polymer according to claim 1, characterized in that The polar monomer has a structure shown in formula (3), Among them, R9 and R 10 Each is independently selected from -H, -F, -Cl, Br, -I, -CN, -COOR, -SO2OR, substituted or unsubstituted -(CH2) k -CH3; R 11 Selected from -H, -F, -Cl, Br, -I, -CN, -COOR, -SO2OR, substituted or unsubstituted -(CH2) p -CH3; R 12 Selected from hydrogen, substituted or unsubstituted -(CH2) m -CH3; R 13 Selected from substituted or unsubstituted -(CH2) n -; R is selected from C1-C6 alkyl; k is an integer from 0 to 20; p is an integer from 0 to 20; m is an integer from 0 to 20; n is an integer from 0 to 20; The substituted substituent is selected from halogen, ester, C1-C 10 Alkyl, C6~C 12 Aryl or C6~C 12 Cycloalkyl.

13. The binder polymer according to claim 12, characterized in that The halogen is selected from fluorine, bromine or chlorine; C1~C 10 The alkyl group is selected from methyl, ethyl, propyl, isopropyl, butyl or tert-butyl; The C6~C 12 Aryl is selected from phenyl, naphthyl or biphenyl; The C6~C 12 Cycloalkyl is selected from cyclohexyl or bicyclohexyl; The ester group is selected from methyl formate, ethyl formate, butyl formate or sulfonate; k is an integer from 0 to 3; p is an integer from 3 to 8; m is an integer from 1 to 7; n is an integer from 0 to 4.

14. The binder polymer according to claim 13, characterized in that The sulfonate group is selected from methyl sulfonate, ethyl sulfonate or propyl sulfonate.

15. The binder polymer according to claim 12, characterized in that R9 and R 10 One of them is hydrogen and the other is C1-C3 alkyl; R 11 Selected from C3-C7 alkyl; R 12 Selected from C1-C6 alkyl; R 13 Selected from a bond or a C1-C3 alkyl group.

16. The binder polymer according to any one of claims 12 to 15, characterized in that A lithium acetate group is connected to the main chain of the polar monomer.

17. The binder polymer according to claim 1, characterized in that The polar monomer has a structure shown in any of the following:

18. The binder polymer according to claim 1, characterized in that The structure of the binder polymer is Wherein X is a rigid monomer, Y is a flexible monomer, Z is a polar monomer, and n is an integer of 20 to 500.

19. The binder polymer according to claim 1, characterized in that Based on the total molar amount of the monomers of the binder polymer, the molar fraction of the rigid monomer is 10% to 50%; and / or, based on the total molar amount of monomers of the binder polymer, the molar fraction of the flexible monomer is 10% to 50%; and / or, based on the total molar amount of monomers of the binder polymer, the molar fraction of the polar monomer is 40% to 80%; And / or, based on the total molar amount of monomers of the binder polymer, the sum of the mole fraction of the rigid monomer and the mole fraction of the flexible monomer is not less than 20% and not more than 60%.

20. The binder polymer according to claim 1, characterized in that The weight average molecular weight of the binder polymer is 50,000 to 600,000; and / or, the viscosity of the binder polymer is 50 cp to 5000 cp; and / or, the dielectric constant of the binder polymer is 5 to 12; And / or, the binder polymer has a glass transition temperature of -50°C to 20°C.

21. A positive electrode sheet, characterized in that: include: A positive electrode active material layer, comprising: a positive electrode active material, a sulfide solid electrolyte and a binder polymer according to any one of claims 1 to 20.

22. The positive electrode sheet according to claim 21, characterized in that: Based on the total mass of the positive electrode active material layer, the content of the positive electrode active material is 50wt.% to 85wt.%; And / or, based on the total mass of the positive electrode active material layer, the content of the sulfide solid electrolyte is 5wt.% to 50wt.%; And / or, based on the total mass of the positive electrode active material layer, the content of the binder polymer is 0.1 wt.% to 10 wt.%.

23. A battery, characterized in that: include: The positive electrode sheet, negative electrode sheet and sulfide solid electrolyte layer as described in claim 21 or 22, wherein the sulfide solid electrolyte layer is located between the positive electrode sheet and the negative electrode sheet.

24. The battery according to claim 23, characterized in that The sulfide solid electrolyte layer comprises a sulfide solid electrolyte and the binder polymer according to any one of claims 1 to 20.

25. An electrical device, characterized in that: Comprising the battery according to claim 23 or 24.

Citation Information

Patent Citations

  • Binder and application thereof

    CN116982176A

  • Composite binder, electrode slurry, electrode plate and all-solid-state battery

    CN117525399A

  • Binder for lithium ion capacitor electrodes, electrode for lithium ion capacitors, and lithium ion capacitor

    JP2015207708A

Cited By

  • Ceramic binder, ceramic slurry and ceramic chip

    CN120208680A

  • Ceramic binder, ceramic slurry and ceramic sheet

    CN120208680B

  • Solid-state battery cell, binder polymer, battery device, and electric device

    WO2026200216A1